PENGARUH GOOD CORPORATE GOVERNANCE DAN LOAN TO DEPOSIT RATIO TERHADAP PROFITABILITAS INDUST1U PERBANKAN DI INDONESIA PERIODE 2012-2014 - Marieta Ariani (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2015)
This study aims to test and analyze: the influence of good corporate governance on the profitability of the banking industri and the influence of loan to deposit ratio on the profitability of the banking industri in Indonesia. The research sample used in the study were 13 banking industries that received the best assessment from the Indonesian Institute for Corporate Directorship (IICD) of the 30 companies listed on the Indonesia Stock Exchange (IDX) as the top 30 issuers with the highest Corporate Governance (CG) scores in the 2012 period -2014. The sampling technique uses purposive sampling method. Data analysis techniques include: descriptive statistics; normality test; classical assumption test: multicollinearity and heteroscedasticity; multiple regression test: test the coefficient of determination, F test, and T test. The results of the study show that: for good corporate governance the number of audit commissions and the number of directors has a significant positive effect on the profitability of the banking industri; institutional ownership and the proportion of independent board of directors have no significant effect on the profitability of the banking industri; and the loan to deposit ratio has a significant negative effect on the profitability of the banking industri in Indonesia.